АРКАЛАРНИ ҲИСОБЛАШ-ЛОЙИҲАЛАШ ВА КОНСТРУКЦИЯЛАШ ЖАРАЁНЛАРИДА MATHCAD ЎҚУВ ДАСТУРИНИНГ ЎРНИ - Набиев, А.Н.; Саидова, Д.Ш. (SCIENCE and SOCIETY, 2024)
The article outlines the relevance of the structural design and calculation of arches, frames and curved beams, as well as the use in educational practice of such educational programs as the Mathcad, Solid Works, KOMPAS-3D, SAM systems.